The effect of early life cytomegalovirus infection on the immune profile of children - Ekman, Ilse; Schroderus, Anna-Mari; Vuorinen, Tytti; Knip, Mikael; Veijola, Riitta; Toppari, Jorma; Ilonen, Jorma; Lempainen, Johanna; Kinnunen, Tuure (Academic Press, 2025)
Cytomegalovirus (CMV) infection has a life-long impact on the immune system, particularly on memory T cells. However, the effect of early life CMV infection on the phenotype and functionality of T cells in infants and especially longitudinal changes occurring during childhood have not been explored in detail. The phenotype and functionality of peripheral blood CD8+ and CD4+ T cells from children infected with CMV in early life (< 6 months of age) was analyzed using high-dimensional flow cytometry. Samples from CMV IgG-seropositive (CMV+) children were collected at 6 months and 6 years of age and compared to samples from CMV-seronegative (CMV-) children. Early life CMV infection caused multiple alterations within T cells. These include downregulation of CD28 expression and upregulation of CD57 expression within both CD27+ early and CD27- late effector memory CD8+ and CD4+ T-cells at 6 months of age. Of these changes, only alterations within the highly differentiated late effector memory compartment persisted at the age of 6 years. Early life CMV-infection has a distinct impact on developing CD8+ and CD4+ memory T cell compartments. It appears to induce both temporary as well as longer-lasting alterations, which may affect the functionality of the immune system throughout life.